2017
DOI: 10.4038/sljb.v2i2.9
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant potential of selected whole grain cereals consumed by Sri Lankans: a comparative in vitro study

Abstract: Whole grains of rice [improved: Bw 361 (red) and Bg 359 (white); traditional: Kalu Heeneti (red) and Suwadal (white)], corn, finger millet, wheat, barley and oat were used in this study. Ethanolic extracts (EEs) and methanolic extracts (MEs) of whole grain cereals were evaluated for total polyphenolic content (TPC), ferric reducing antioxidant power (FRAP), oxygen radical absorbance capacity (ORAC), DPPH and ABTS radical scavenging antioxidant properties (AP) in vitro (n=3 each). Results showed significant dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…There were no significant differences (P ≥ 0:05) between the ORAC values of ethanolic and methanolic extracts in Ravi and Oshadha varieties. ORAC values of common cereals were reported in previous studies [30]. ORAC values of methanolic extracts of white and red rice varieties ranged from 150.61 to 439.64 mg trolox equivalents per 100 g of flour on a dry weight basis, while ORAC values of ethanolic extracts ranged from 108.32 to 272.08 mg trolox equivalents per 100 g of flour on a dry weight basis.…”
Section: Oxygen Radical Absorbancesupporting
confidence: 56%
See 1 more Smart Citation
“…There were no significant differences (P ≥ 0:05) between the ORAC values of ethanolic and methanolic extracts in Ravi and Oshadha varieties. ORAC values of common cereals were reported in previous studies [30]. ORAC values of methanolic extracts of white and red rice varieties ranged from 150.61 to 439.64 mg trolox equivalents per 100 g of flour on a dry weight basis, while ORAC values of ethanolic extracts ranged from 108.32 to 272.08 mg trolox equivalents per 100 g of flour on a dry weight basis.…”
Section: Oxygen Radical Absorbancesupporting
confidence: 56%
“…TPCs of common cereals were reported by Abeysekera et al [30]. According to their findings, TPCs of methanolic extracts of white and red rice varieties ranged from 29.34 to 139.79 mg GAEs per 100 g of flour on a dry weight basis, while TPCs of ethanolic extracts ranged from 59.78 to 113.56 mg GAEs per 100 g of flour on a dry weight basis.…”
Section: Resultsmentioning
confidence: 78%
“…Recent studies conducted in Sri Lanka scientifically proved that the rice varieties tested in the present study had high amounts of phenolic antioxidants, tocopherols and γ-oryzanols [8][9][10]17,34]. Therefore, presence of such compounds in brans of these rice varieties may be at least partly responsible for the observed physiological radical scavenging activities.…”
Section: Discussionmentioning
confidence: 51%
“…Zhao et al, 2014 reported that TPC of legumes extracts ranged 9.5 -47.6 mg (GAE) /g [10]. Further it was reported that the TPC of legumes were significantly higher than that corn, millets, wheat and rice [19] [26]. The data reported by , analyzing twenty one varieties of legumes, the TPC ranged from 0.57 -9.60 mg (GAE)/g were in the same range of our varieties [27].…”
Section: Total Phenolic Content (Tpc)mentioning
confidence: 99%
“…The ground grain powder (2.5 g) and 20 times the sample weight of volume of 70% ethanol were shaken overnight at room temperature (25 ± 2°C). Extracts were then centrifuged at 3000 g for 15 min, supernatant filtered through syringe filters, evaporated under vacuum in a rotary evaporator and resulted solution was freeze dried at -40 0 C, 18 h, 0.1 mbar [19].…”
Section: Sample Extractionmentioning
confidence: 99%